Induction of labour versus expectant management for large-for-date fetuses: a randomised controlled trial. Issue 9987 (27th June 2015) - Boulvain, Michel; Senat, Marie-Victoire; Perrotin, Franck; Winer, Norbert; Beucher, Gael; Subtil, Damien; Bretelle, Florence; Azria, Elie; Hejaiej, Dominique; Vendittelli, Françoise; Capelle, Marianne; Langer, Bruno; et al.
Summary: Background: Macrosomic fetuses are at increased risk of shoulder dystocia. We aimed to compare induction of labour with expectant management for large-for-date fetuses for prevention of shoulder dystocia and other neonatal and maternal morbidity associated with macrosomia. Methods: We did this pragmatic, randomised controlled trial between Oct 1, 2002, and Jan 1, 2009, in 19 tertiary-care centres in France, Switzerland, and Belgium. Women with singleton fetuses whose estimated weight exceeded the 95th percentile, were randomly assigned (1:1), via computer-generated permuted-block randomisation (block size of four to eight) to receive induction of labour within 3 days between 37 +0 weeks and 38 +6 weeks of gestation, or expectant management. Randomisation was stratified by centre. Participants and caregivers were not masked to group assignment. Our primary outcome was a composite of clinically significant shoulder dystocia, fracture of the clavicle, brachial plexus injury, intracranial haemorrhage, or death. We did analyses by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00190320 . Findings: We randomly assigned 409 women to the induction group and 413 women to the expectant management group, of whom 407 women and 411 women, respectively, were included in the final analysis. Mean birthweight was 3831 g (SD 324) in the induction group and 4118 g (392) in the expectant group. Induction of labour significantly reduced the risk of shoulder dystocia or associated morbidity (n=8) compared with expectant management (n=25; relative risk [RR] 0·32, 95% CI 0·15–0·71; p=0·004). We recorded no brachial plexus injuries, intracranial haemorrhages, or perinatal deaths. The likelihood of spontaneous vaginal delivery was higher in women in the induction group than in those in the expectant management group (RR 1·14, 95% CI 1·01–1·29). Caesarean delivery and neonatal morbidity did not differ significantly between the groups. Interpretation: Induction of labour for suspected large-for-date fetuses is associated with a reduced risk of shoulder dystocia and associated morbidity compared with expectant management. Induction of labour does not increase the risk of caesarean delivery and improves the likelihood of spontaneous vaginal delivery. These benefits should be balanced with the effects of early-term induction of labour. Funding: Assistance Publique–Hôpitaux de Paris and the University of Geneva.